Determinants of cigarette smoking among school adolescents in eastern Ethiopia: a cross-sectional study - Reda Ayalu A; Moges Asmamaw; Yazew Berhanu; Biadgilign Sibhatu (Harm Reduction Journal, 2012)
Abstract Background The World Health Organization (WHO) attributes more than 4 million deaths a year to tobacco, and it is expected that this figure will rise to 10 million deaths a year by 2020. Moreover, it is now a growing public health problem in the developing world. Objective To assess the prevalence of cigarette use and its determinant factors among high school students in eastern Ethiopia. Methods A cross-sectional study was conducted using structured self-administered questionnaires among 1,721 school adolescents in Harar town, eastern Ethiopia. Univariate and multivariate logistic regression analyses were performed to examine associations. Results The analysis revealed that prevalence of ever cigarette smoking was 12.2% (95% CI 10.8% - 13.9%). Reasons mentioned for smoking cigarettes were for enjoyment (113, 52.8%), for trial (92, 42.9%), and for other reasons (9, 4.3%). The main predictors of cigarette smoking were sex (OR 4.32; 95% CI 2.59-7.22), age (OR 1.20; 95% CI 1.05-1.38) and having friends who smoke (OR 8.14; 95% CI 5.19-12.70). Living with people who smoke cigarettes was not significantly associated with smoking among adolescents (OR 1.25; 95% CI 0.81-1.92). Conclusion This study concluded that high proportion of school adolescents in Harar town smoked cigarettes. Sex, age and peer influence were identified as important determinants of smoking. There is a need for early cost-effective interventions and education campaigns that target secondary school students.